(3GSJNQGL GdChJGQ aj GdOGFQI HNhGU GdNW GdefMfi GdhGbY ajgGs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3GdehUd s)
(3ChdgG (B:s
(3hbaJ Ydi eG GSJYedJfjg ef GdSHH GdOGYi EjGi Edi GdhdhY HJUMjM OYhi GdbOeGA GdjhfGfjjf s
(3BNQgG (B:s
(3Yf Ybdc UOi GdZadI hJJhUd Hg Edi eGjOb Yf CagGe GdYhGe , hjfMSe Hjfi hHjfc s
(3aQY GdeDda ef JUfjag SfI (B418 (3g`s
(3hHgG CTcGd gfOSjI cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
Keywords: (3GdQjGVjGJs